2003
DOI: 10.1097/00000542-200304000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Erythrocyte Concentrate Storage Time on Postsurgical Morbidity in Cardiac Surgery Patients

Abstract: Prolonged storage of erythrocytes does not increase morbidity in cardiac surgery. However, storage for longer than 28 days could be a risk factor for the acquisition of nosocomial pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
155
3
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 30 publications
9
155
3
5
Order By: Relevance
“…The emphasis over the last several decades has been on lesions that develop over the storage period. Observational studies in trauma, critical illness, and cardiac surgery, linking the administration of older blood to increased mortality (3)(4)(5), support the concern that transfusion of older blood may be detrimental. Evidence also exists that transfusion is detrimental in some settings regardless of RBC storage duration.…”
Section: H) P Values Represent Comparison Between Values In Rbcs Assmentioning
confidence: 98%
See 1 more Smart Citation
“…The emphasis over the last several decades has been on lesions that develop over the storage period. Observational studies in trauma, critical illness, and cardiac surgery, linking the administration of older blood to increased mortality (3)(4)(5), support the concern that transfusion of older blood may be detrimental. Evidence also exists that transfusion is detrimental in some settings regardless of RBC storage duration.…”
Section: H) P Values Represent Comparison Between Values In Rbcs Assmentioning
confidence: 98%
“…However, numerous changes occur in RBCs during storage (collectively referred to as the ''storage lesion'') that may alter their biological function, including delivery of oxygen to cells (2). Retrospective cohort studies have found a correlation between RBC storage duration and morbidity and mortality rates after transfusion (3)(4)(5), suggesting progressive storage lesions may be responsible for adverse outcomes. Despite these observational data, no large controlled clinical trials have been conducted to evaluate the relationship between the age of stored RBCs and clinical outcomes.…”
mentioning
confidence: 99%
“…Concern has also been expressed about the quality of stored blood and observations of negative outcomes in transfused patients. Retrospective studies found higher mortality and morbidity rates after transfusion that correlated with the duration of RBC storage [12][13][14][15]. This suggested that changes in RBC function during storage may be responsible for adverse outcomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Immunomodulation with down-regulation of cellular immune function increases the risk of nosocomial infections [3,4] . Furthermore, transfusion of older blood raises the incidence of serious complications and increases time to ventilation [5][6][7] . Transfusion related acute lung injury, an uncommon but probably underestimated complication, is one of the leading causes of transfusion-related mor-bidity and mortality [8,9] .…”
Section: Introductionmentioning
confidence: 99%